Pendidikan Karakter Cinta Lingkungan melalui Kegiatan Menanam Hidroponik bagi Anak Usia Dini di TKS Kartika V 16 - Zainal Abidin; Roby Roby; Daryono Daryono; F. Silvi Dwi Mentari; Yuanita Yuanita; Nur Hidayat; Faradilla Faradilla; La Mudi; Riama Rita Manullang; Rusmini Rusmini; Haryatie Sarie; Mujibu Rahman; Andi Lisnawati (Jurnal Kemitraan Masyarakat, 2025)
Environmental character education from an early age is a strategic step in developing a generation that cares about the natural world. Instilling this value is crucial in concrete ways so that children can understand and directly experience the benefits of protecting the environment. One effort undertaken is through a simple hydroponic learning activity involving children from TKS Kartika V 16. The activity was held once at the Samarinda State Agricultural Polytechnic with the support of lecturers as resource persons. Through a hands-on learning method, the children were introduced to how to grow lettuce and bok choy using a simple hydroponic system. The learning process included an introduction to tools and materials, an explanation of the planting stages, and plant care. Observations throughout the activity showed high enthusiasm among the children. They were actively involved, from preparing the planting medium, planting the seeds, to providing air and nutrients to the plants. This activity fostered a sense of care and responsibility for the plants they grew themselves. Furthermore, the children's fine motor skills were also demonstrated through activities such as arranging the planting medium, sowing the seeds, and assembling the hydroponic equipment. This activity not only developed individual skills but also taught social values such as cooperation and mutual assistance. Children learn to work in groups, help each other, and appreciate each other's roles in the planting process. This hands-on, hands-on approach has proven effective in strengthening environmental awareness in a fun and contextual way. Therefore, environmental education through hydroponics can be a practical, inspiring, and easy-to-implement learning medium for young children, while also serving as a concrete example of how character education can go hand-in-hand with the introduction of environmentally friendly technologies.